Evaluation of antibiotic sensitivity of potential probiotic Bacillus strains isolated from chicken and pig feces - Nguyen, Hai Van; Nguyen, Lan Anh; Nguyen, Thi Minh Duc; Vu, Thi Hanh Nguyen; Phi, Quyet Tien; Nguyen, Ha Anh; Ho, Phu Ha (Vietnam Journal of Science and Technology, 2022)
Nowadays, the misuse and overuse of antibiotics in livestock production leads to the appearance of antibiotic resistant strains that promotes the use of probiotics in feed to minimise/replace antibiotic consumption. Among them, Bacilli are common supplements for feed effectiveness and livestock health benefits. However, there is a growing concern about the development of antibiotic resistance and transfer of antibiotic resistance genes among bacteria. Thus, the European Food Safety Authority (EFSA) has suggested that products containing Bacillus strains intended to use as feed additive must be examined for susceptibility to antimicrobials of human and veterinary importance. In this study, the antibiotic susceptibility of potential probiotic Bacillus strains was investigated. A total of 59 Bacillus species were isolated from 10 samples of chicken and pig feces. Then, the in vitro probiotic characteristics including low pH tolerance, catalase activity, protease, amylase and cellulase enzymes production were tested to select appropriate isolates for further studies. Thirty-three promising probiotic strains were assessed for their antibiotic susceptibility against 13 antibiotics by disc diffusion method. In most cases, isolated Bacillus strains were susceptible to tested antibiotics. The obtained results demonstrated the potential application of Bacillus spp. as feed supplements in animal production.